In vitro evaluation of PKE prebiotic on lactobacillus SP - Chen, Wei Li; Liang, Juan Boo; Jahromi, Mohammad Faseleh; Ho, Yin Wan; Abdullah, Norhani (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Palm kernel expeller had been viewed as a by-product with high fiber content, mainly in the form of mannan, with cellulose and xylan making up the remaining portion. Partial hydrolysis of these hemicelluloses will produce short chain oligosaccharides, representing a good source of prebiotic oligosaccharides. The aim of this study was to increase the content of PKE oligosaccharides using heat and enzymes and evaluates its efficacy in supporting growth of Lactobacillus sp. in vitro. Results showed that PKE oligosaccharides can support growth of three different Lactobacillus sp. (P<0.05), and highest growth was observed in steam + enzyme treatment. This study showed the potential of PKE as a source of prebiotic in supporting growth of Lactobacillus sp.